2016
DOI: 10.1088/1748-605x/12/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biological performance of injectable and degradable calcium phosphate cement

Abstract: Enhancing degradation of poorly degrading injectable calcium phosphate (CaP) cements (CPCs) can be achieved by adding poly(lactic-co-glycolic acid) (PLGA) microparticles, generating porosity after polymer degradation. CPC-PLGA has proven to be biodegradable, although its long-term biological performance is still unknown. Optimization of injectability could be achieved via addition of carboxymethyl cellulose (CMC). Here, we evaluated the long-term in vivo performance of CPC-PLGA with or without the lubricant CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…Modified Urist method can properly preserve and release BMP cytokines [7, 8]. BMP is capable of inducing cells with osteogenic potential to differentiate into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Modified Urist method can properly preserve and release BMP cytokines [7, 8]. BMP is capable of inducing cells with osteogenic potential to differentiate into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…As CPCs first form into a paste, they can be molded into arbitrarily shaped bone defect sites and set under physiological conditions, which enables them to be utilized in minimally invasive surgical procedures . These characteristic handling and biological properties have prompted CPCs to garner much attention in the dental and orthopedic field as an attractive alternative to other conventional bone substitute materials . Moreover, CPCs do not exhibit many of the complications associated with auto‐ and allografts such as donor site morbidity and chronic pain, surgical harvesting, limited availability, and risk of disease transfer and/or infection .…”
Section: Introductionmentioning
confidence: 99%
“…These characteristic handling and biological properties have prompted CPCs to garner much attention in the dental and orthopedic field as an attractive alternative to other conventional bone substitute materials . Moreover, CPCs do not exhibit many of the complications associated with auto‐ and allografts such as donor site morbidity and chronic pain, surgical harvesting, limited availability, and risk of disease transfer and/or infection . Nevertheless, the clinical applicability of CPCs has remained limited due to two factors: (i) poor degradability due to a lack of interconnected macroporosity to allow for vascularization and bone tissue ingrowth and (ii) poor cohesion and washout resistance, which is especially important when considering their indications for skeletal sites where perfusion is high, such as the spine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Previous work has shown that chemical characteristics of PLGA (i.e., acid-terminated or end-capped), porogen type (i.e., dense or hollow), and size all influence the degradation of CPC-PLGA composites. 13 Although CPC-PLGA demonstrated superiority regarding material degradation and bone formation after a prolonged implantation period of 6 months, initial bone formation was delayed. 12 These pores create macroporosity within the ceramic CPC matrix, which allows for fluid flow and tissue ingrowth, especially when the created pores are interconnected.…”
Section: Introductionmentioning
confidence: 99%